Sink or Swim? Clinical Objective Tests and Measures Associated with Shoulder Pain in Swimmers of Varied Age Levels of Competition: A Systematic Review - June Kennedy; Thomas Otley; Steph Hendren; Heather Myers; Angela Tate (International Journal of Sports Physical Therapy)
# BACKGROUND